2x+23=-4x+47

Simple and best practice solution for 2x+23=-4x+47 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+23=-4x+47 equation:



2x+23=-4x+47
We move all terms to the left:
2x+23-(-4x+47)=0
We get rid of parentheses
2x+4x-47+23=0
We add all the numbers together, and all the variables
6x-24=0
We move all terms containing x to the left, all other terms to the right
6x=24
x=24/6
x=4

You can always share this solution

See similar equations:

| -6x+17=-19 | | 4x²+8x-9=0 | | 5x/2+4=7x | | 5x/2-4=7x | | 16+6z=10 | | x-30/100=338 | | x(22/100)=15,000 | | Y=x2-12x-5 | | X^(2)=4-6x | | 15b+50=35 | | 17(5)^x=7(2)^x | | ((5x)/(2))+4=7x | | 4/3x-1+(2x+3)(2x-3)/12-(2x+3)2=2/3x-9x-3/6 | | 4/3x-1+(2x+3)(2x-3)/12-(2x+3)^2=2/3x-9x-3/6 | | 40x+10(1.5x)=1600 | | p+6p?5p=20 | | 4x^2-70x+150=0 | | 2x2+5x-8=0 | | 7x=3x+12=2x+5= | | 7x=3x+122x+5= | | 3/d+2=9 | | 50.?56+x=?12?23 | | 2*(x+8)=20 | | 22*x=226 | | 4n+12+3n=82 | | 2*(x+4)=14 | | 10=90(1/2)^x | | 17–x=9x= | | 5*(x-3)=15 | | 8*(x+2)=48 | | 4x+66=10x+12x= | | 12x-3x-36000=0 |

Equations solver categories